Effect of the fluid management nursing intervention on improving biochemical test results and dialysis therapy in chronic kidney disease patients: a randomized controlled trial - de Souza Maciel Ferreira, José Erivelton; Freire de Sousa , Daniel; Pessoa Moreira, Rafaella; Cândido Morais, Huana Carolina; Moreira Barros, Lívia; Frota Cavalcante, Tahissa (Investigación y Educación en Enfermería, 2025)
Objetive. To test the effectiveness of nursing intervention to control fluid volume on improving laboratory test results and dialysis adequacy in patients with Excess fluid volume. Methods. This is a randomized, double-blind, parallel-group controlled trial involving 34 patients with chronic kidney disease and a nursing diagnosis of Excess Fluid Volume undergoing chronic hemodialysis equally randomized into two groups (control n=17 and intervention n=17). Data were collected on sociodemographic and clinical factors, the presence of Excess Fluid Volume, and water balance. Laboratory parameters, including serum electrolytes, urea, creatinine, and dialysis adequacy markers, were assessed before and after the intervention. The intervention consisted of 13 nursing activities, including educational, follow-up, and reminder components, such as fluid balance monitoring, daily weight control, edema assessment, laboratory follow-up, and health education on diet and self-care. The control group received only the usual care provided at the dialysis clinic. Results. There were significant improvements in laboratory test results and dialysis adequacy. The statistical difference between the groups was significant in the mean values of calcium (p<0.001), post-hemodialysis urea (p=0.002), and creatinine (p=0.006), demonstrating the direct effect of the intervention. In addition, there were improvements in overall dialysis quality and adequacy measures. Conclusion. The nursing intervention significantly improved laboratory test results and dialysis adequacy in patients with chronic renal failure and Excess Fluid Volume, highlighting its potential for enhancing patient management and nursing care.